Co-complexes on modified graphite surface for steady green hydrogen production from water at neutral pH - Toledo-Carrillo, Esteban A.; García-Rodríguez, Mario; Morallón, Emilia; Cazorla-Amorós, Diego; Ye, Fei; Kundi, Varun; Kumar, Priyank V.; Verho, Oscar; Dutta, Joydeep; Åkermark, Bjorn; Das, Biswanath (Frontiers in Chemistry, 2024)
Green hydrogen production from water is one attractive route to non-fossil fuel and a potential source of clean energy. Hydrogen is not only a zero-carbon energy source but can also be utilized as an efficient storage of electrical energy generated through various other sources, such as wind and solar. Cost-effective and environmentally benign direct hydrogen production through neutral water (∼pH 7) reduction is particularly challenging due to the low concentration of protons. There is currently a major need for easy-to-prepare, robust, as well as active electrode materials. Herein we report three new molecular electrodes that were prepared by anchoring commercially available, and environmentally benign cobalt-containing electrocatalysts with three different ligand frameworks (porphyrin, phthalocyanine, and corrin) on a structurally modified graphite foil surface. Under the studied reaction conditions (over 7 h at 22°C), the electrode with Co-porphyrin is the most efficient for the water reduction with starting ∼740 mV onset potential (OP) (vs. RHE, current density 2.5 mA/cm2) and a Tafel slope (TS) of 103 mV/dec. It is followed by the molecular electrodes having Co-phthalocyanine [825 mV (OP), 138 mV/dec (TS)] and Vitamin-B12 (Co-corrin moiety) [830 mV (OP), 194 mv/dec (TS)]. A clear time-dependent improvement (>200 mV over 3 h) in the H2 production overpotential with the Co-porphyrin-containing cathode was observed. This is attributed to the activation due to water coordination to the Co-center. A long-term chronopotentiometric stability test shows a steady production of hydrogen from all three cathode surfaces throughout seven hours, confirmed using an H2 needle sensor. At a current density of 10 mA/cm2, the Co-porphyrin-containing electrode showed a TOF value of 0.45 s−1 at 870 mV vs. RHE, whereas the Co-phthalocyanine and Vitamin-B12-containing electrodes showed 0.37 and 0.4 s−1 at 1.22 V and 1.15 V (vs. RHE), respectively.